Chokora - Surviving on the street - Furrer, Lea (Switzerland, 2010)
With a film camera, youths Anthony and Robert from Nairobi document and comment upon life on the streets and in the Halfway Center. Thereby, not only their trials and tribulations, but also their sense of humor and their plans for the future, are expressed. Moving images which convince through their authenticity relate their hopes for the future. By handing over the camera to the two protagonists, a dynamic change of perspectives is established to render possible a differentiated examination of the subject matter as well as the proceedings of the film
Verzio Film Festival Submission
Keywords: Documentary films